The process of international legal reproduction : inequality, historiography, resistance / Rose Parfitt. - Parfitt, Rose (Cambridge studies in international and comparative law. New series, 2019)
That all states are free and equal under international law is axiomatic to the discipline. Yet even a brief look at the dynamics of the international order calls that axiom into question. Mobilising fresh archival research and drawing on a tradition of unorthodox Marxist and anti-colonial scholarship, Rose Parfitt develops a new 'modular' legal historiography to make sense of the paradoxical relationship between sovereign equality and inequality. Juxtaposing a series of seemingly unrelated histories against one another, including a radical re-examination of the canonical story of Fascist Italy's invasion of Ethiopia, Parfitt exposes the conditional nature of the process through which international law creates and disciplines new states and their subjects. The result is a powerful critique of international law's role in establishing and perpetuating inequalities of wealth, power and pleasure, accompanied by a call to attend more closely to the strategies of resistance that are generated in that process.